Green Firm‐Specific Advantages for Enhancing Environmental and Economic Performance. Issue 1 (November 2014) - Singh, Nitish; Park, Yung‐Hwal; Tolmie, Carri R.; Bartikowski, Boris
<x xml:space="preserve">Abstract</x> One of the most important determinants of a firm's motivation to invest in higher environmental performance is whether such investments will lead to higher economic returns. Although several studies have explored links between environmental and economic performance, strategic insights into which capabilities and resources drive improved environmental and economic performance are lacking. Nine green firm‐specific advantages (Green FSAs) can facilitate the implementation and enhancement of environmental management practices related to planning, organization, operations, and communications. They are ecosystem services internalization Green FSAs, sustainable thinking Green FSAs, cradle‐to‐cradle Green FSAs, eco‐efficiency Green FSAs, eco‐innovation Green FSAs, solution‐oriented Green FSAs, sustainable reputation Green FSAs, eco‐networking Green FSAs, and localized Green FSAs. These Green FSAs have the potential not only to increase environmental performance, but also to enhance efficiency, reduce waste, improve compliance measures, and save additional costs, all of which will ultimately result in higher levels of economic performance. © 2014 Wiley Periodicals, Inc.